Sugar Plum ballerinas - Plum fantastic - Goldberg, Whoopi 1955- (Disney/Jump at the Sun Books, 2008)
When her mother moves the family to Harlem and enrolls her in the Nutcracker School of Ballet, reluctant dancer Alexandrea is picked to be the Sugar Plum Fairy in the big recital
Forts. bildet: Toeshoe trouble
Keywords: Schwarze. USA; Ballet dancing; Friendship; African Americans; Harlem (New York, N.Y.); Jugendbuch